Is there any relationship between mutation in CPS1 Gene and pregnancy loss? - Mehrdad Talebi; Mohammad Yahya Vahidi Mehrjardi; Kambiz Kalhor; Mohammadreza Dehghani (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background Carbamoyl phosphate synthetase 1 (CPS1) is a liver-specific enzyme with the lowest enzymatic rate, which determines the overall rate of the other reactions in the pathway that converts ammonia to carbamoyl phosphate in the first step of the urea cycle. Carbamoyl phosphate synthetase 1 deficiency (CPS1D), which usually presents as lethal hyperammonemia, is a rare autosomal recessive hereditary disease. Case We report a case of a two-day-old female neonate with lethal hyperammonemia. The newborn infant was presented with hyperammonemia (34.7 μ g/ml; reference range 1.1-1.9). In Plasma amino acid analysis, there was a significant elevated levels of alanine (3,004 μ mol/L; reference range, 236-410 μ mol/L), glutamine (2,256 μ mol/L; reference range, 20-107 μ mol/L), asparagine (126 μ mol/L; reference range, 30-69 μ mol/L), glutamic acid (356 μ mol/L; reference range, 14-192 μ mol/L), aspartic acid (123 μ mol/L; reference range, 0-24 μ mol/L), and lysine (342 μ mol/L; reference range, 114-269 μ mol/L). We cannot diagnose the urea cycle disorder (UCD) CPS1D properly only based on the quantity of biochemical intermediary metabolites to exclude other UCDs with similar symptoms. Following next generation sequencing determined one homozygous mutation in CPS1 gene and also this mutation was determined in her parents. The identified mutation was c.2758G > C; p.Asp920His, in the 23 exon of CPS1. This novel homozygous mutation had not been reported previously. Conclusion We applied whole exome sequencing successfully to diagnose the patient with CPS1D in a clinical setting. This result supports the clinical applicability of whole exome sequencing for cost-effective molecular diagnosis of UCDs.